A Novel Double-Sided Electromagnetic Dog Clutch with an Integrated Synchronizer Function - Bogdan Miroschnitschenko; Florian Poltschak; Wolfgang Amrhein (Actuators)
Dog clutches are superior to synchromesh units due to much less wear caused by friction but require an external torque source to synchronize the rotation speeds. The current trend in e-mobility to use the driving motor of an electric vehicle as this source just creates another problem, which is known as torque holes. In this work, we propose a novel double-sided dog clutch that synchronizes the speeds electromagnetically by itself avoiding mechanical contact between the parts. A shift sleeve, two coils placed coaxially in their stators, and two complementary rings form an electromagnetic reluctance actuator, which is integrated inside the gearbox between two gearwheels and represents the double-sided clutch. Thus, intermediate parts between the shift sleeve and the actuator are not required. Both actuator sides can produce axial force and electromagnetic torque. However, torques and forces are generated simultaneously on both sides. Therefore, a special control algorithm is developed to keep the resulting axial force approximately equal to zero while the torque is generated in the neutral gear position. After the synchronization, the axial force is applied on the corresponding side to shift the required gear engaging the shift sleeve teeth directly with the slots of the complementary ring mounted on the gearwheel. So, an axial contact of the teeth at an unaligned state, which can lead to unsuccessful shifting, is avoided. A testrig, which includes a clutch prototype and a testing two-speed gearbox, has been designed and built. The developed theoretical ideas have been verified during the experiments under different conditions. The experiments confirm that the actuator can reduce positive and negative speed differences on both sides and subsequently shift the gear without a shift sleeve collision at misaligned angular positions.